Mysticism as a Philosophical Foundation of Maurice Maeterlinck’s Symbolist Theater - Dubinina, Kateryna (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
The relevance of this topic is determined by the scientific novelty of the research approach to studying the dramaturgy of M. Maeterlinck, his worldview ideas based on mysticism, as well as the need to trace the influence of the playwright’s symbolism on contemporary culture, contemporary theater, and literature. This article attempts to analyze and trace how the concepts of mysticism became the basis for the creation of Maeterlinck’s unique theatrical world, what elements of mysticism are present in his plays and essays, and how they shape the atmosphere and themes of his works. Thus, the article determines that the playwright’s worldview was formed under the influence of his fascination with the "philosophy of life" of A. Schopenhauer and F. Nietzsche, as well as his religiosity and freedom of artistic thought. The interconnection between mysticism and symbolism is traced, the essence of mysticism as a trend, its concepts and ideas are revealed in order to compare them with the postulates and worldview ideas of M. Maeterlinck, which are highlighted in his plays and philosophical essays. Therefore, the scientific research proves that in the context of European literary mysticism, Maeterlinck’s symbolism should be understood through the prism of universal truths and the search for the meaning of existence, which are in some opposition to traditional dogmatic Christian ideas, precisely because of their mystical and gnostic character. It is revealed that Maeterlinck’s mysticism manifests itself through the symbols of silence, statics, stillness, darkness as something that not only can cause anxiety and fear of the Unknown but is also able to stop, evoke a desire to be silent, to hear and immerse oneself in the knowledge of this Unknown.